Phylogenetic Variants of Rickettsia africae, and Incidental Identification of "Candidatus Rickettsia Moyalensis" in Kenya. - Gathii Kimita; Beth Mutai; Steven Ger Nyanjom; Fred Wamunyokoli; John Waitumbi (Public Library of Science (PLoS), 2016)
BACKGROUND:Rickettsia africae, the etiological agent of African tick bite fever, is widely distributed in sub-Saharan Africa. Contrary to reports of its homogeneity, a localized study in Asembo, Kenya recently reported high genetic diversity. The present study aims to elucidate the extent of this heterogeneity by examining archived Rickettsia africae DNA samples collected from different eco-regions of Kenya. METHODS:To evaluate their phylogenetic relationships, archived genomic DNA obtained from 57 ticks a priori identified to contain R. africae by comparison to ompA, ompB and gltA genes was used to amplify five rickettsial genes i.e. gltA, ompA, ompB, 17kDa and sca4. The resulting amplicons were sequenced. Translated amino acid alignments were used to guide the nucleotide alignments. Single gene and concatenated alignments were used to infer phylogenetic relationships. RESULTS:Out of the 57 DNA samples, three were determined to be R. aeschlimanii and not R. africae. One sample turned out to be a novel rickettsiae and an interim name of "Candidatus Rickettsia moyalensis" is proposed. The bonafide R. africae formed two distinct clades. Clade I contained 9% of the samples and branched with the validated R. africae str ESF-5, while clade II (two samples) formed a distinct sub-lineage. CONCLUSIONS:This data supports the use of multiple genes for phylogenetic inferences. It is determined that, despite its recent emergence, the R. africae lineage is diverse. This data also provides evidence of a novel Rickettsia species, Candidatus Rickettsia moyalensis.